2003
DOI: 10.4315/0362-028x-66.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Lactic Acid Bacteria with Human Intestinal Epithelial Cells: Effects on Cytokine Production

Abstract: As a participant in the mucosal immune response, the intestinal epithelial cell must respond to a variety of stimuli, including lactic acid bacteria (LAB) consumed in the diet. The objective of this study was to compare the abilities of several strains of LAB to modulate cytokine secretion by human intestinal epithelial cell (IEC) line HT-29. Certain strains of Lactobacillus rhamnosus, Lactobacillus delbrueckii, and Lactobacillus acidophilus suppressed the production of the chemokine RANTES by stimulated HT-29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 37 publications
7
56
0
2
Order By: Relevance
“…intestinal epithelial cell line (Wallace et al, 2003). Together with our findings, it appears that inhibition of IL-8 production may be part of the mechanism by which lactobacilli impart their welfare to the gut.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…intestinal epithelial cell line (Wallace et al, 2003). Together with our findings, it appears that inhibition of IL-8 production may be part of the mechanism by which lactobacilli impart their welfare to the gut.…”
Section: Discussionsupporting
confidence: 53%
“…The lactobacilli have also been shown to stimulate the immune system and regulate cytokine production. They suppress synthesis of interleukin (IL)-8, transforming growth factor (TGF-β), and tumour necrosis factor (TNF-α) by the intestinal epithelial cells (Reid et al, 2001;Wallace et al, 2003). Further, when administered intravenously, lactobacilli cultivation products induce the expression of a putative protective protein (Hsp70) in the rat heart that subsequently protects the heart against ischaemia and reperfusion tachyarrhythmia (Oxman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Commensal bacteria can inhibit inflammatory pathways and perhaps contribute to the maintenance of homeostasis [75] . In vitro experiments show that a wide range of commensal bacteria can reduce inflammatory signaling in intestinal epithelia by inhibition of the NF-κB signaling pathway [76,77] . Preliminary work suggests that early colonization by probiotics (facultative anaerobes such as Lactobacilli and Bifidobacteria) reduces the risk of NEC in very low birth weight infants [78,79] .…”
Section: Patent Ductus Arteriosismentioning
confidence: 99%
“…Wallace et al 9) reported that lactic acid bacteria regulated the expression of cytokines in IECs. Moreover, Klimpel et al 10) observed S. typhimurium-induced cytokine productions in intestinal tracts, and Marc et al 11) reported E. coli-induced expression of IL-6 in Caco-2 cells.…”
mentioning
confidence: 99%